2018
DOI: 10.1111/eve.12897
|View full text |Cite
|
Sign up to set email alerts
|

Transmaxillary anchored silicon embedded gauze plug in the post‐operative treatment of a large oromaxillary fistula caused by a supernumerary cheek tooth

Abstract: Summary A 9‐year‐old Hungarian sport horse gelding was presented to the clinic in poor condition displaying malodorous bilateral purulent nasal discharge. Oral examination revealed the presence of supernumerary 111 and 211. Bilateral diastema formation between the third maxillary molars and the supernumerary teeth with deep periodontal pockets and massive food impactions were diagnosed endoscopically. Radiography revealed inhomogenous sinus opacities in the left and right paranasal sinuses. Following bilateral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
8
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 17 publications
0
8
0
2
Order By: Relevance
“…The technique described by Hevesi et al . () to obturate the fistula with a gauze‐cored silicone plug fulfils the criteria above and was successful in this case. However, the authors reported that in the beginning, the silicone plug was inserted too deeply into the fistula, which impeded the healing process.…”
mentioning
confidence: 70%
See 4 more Smart Citations
“…The technique described by Hevesi et al . () to obturate the fistula with a gauze‐cored silicone plug fulfils the criteria above and was successful in this case. However, the authors reported that in the beginning, the silicone plug was inserted too deeply into the fistula, which impeded the healing process.…”
mentioning
confidence: 70%
“…In the case described by Hevesi et al . (), the alveolar healing led to the closure of the smaller fistula in the left arcade (211/s211). Granulation in the alveolus 111/s111 decreased the diameter of the fistula but did not close it.…”
mentioning
confidence: 99%
See 3 more Smart Citations